The Role of Teacher's Feedback in Physical Education: Motivational Climate as Mediator - (:unkn) unknown (HACETTEPE UNIV, 2018)
The aim of this study was to investigate the role of perceived teachers' feedback on the relationship among students' perceptions of motivational climate, intrinsic and extrinsic motivations, enjoyment and concentration in physical education lessons. Total of 835 middle school students (M-Age= 12.83 +/- 0.67) voluntarily participated to the cross-sectional data collection. Convenience sampling was used to select schools from Denizli. Structural Equation Modelling showed that knowledge of performance feedback positively predicted perceived performance approach climate and perceived mastery climate positively predicted enjoyment, concentration and intrinsic motivation. Furthermore, perceived motivational climate was not found to mediate the relationship among perceived teacher feedback, motivation and lesson engagement. The results were discussed in terms of implications for physical education environment.
Keywords: Perceived teachers' feedback; perceived motivational climate; motivation; enjoyment; concentration; physical education; INTRINSIC MOTIVATION; GOAL ORIENTATIONS; POSITIVE FEEDBACK; ACHIEVEMENT GOALS; PERCEPTIONS; STUDENTS; SELF; COMPETENCE; SPORT; INFORMATION